”Damfotbollen- visst har den en framtid” : Damfotbollens tidiga utveckling i Luleå under 1970-talet. - Reimegård, Erik (2015)
The purpose of this essay has been to examine the early development of women’s football in Luleå, Sweden. The geographical delimitation Luleå refers to Luleå municipality. The delimitation in time is 1970-1979. The method of the study is partly quantitative, in order to examine how many teams where active which years, partly qualitative in order to examine how and why women’s football teams were founded and what type of challenges the teams and players faced. The result shows a motley growth of women´s football teams over the period. That the teams rarely or seldom were formed out of already existing social groups. The results also show that several of the teams and players faced various difficulties, there are even examples of women teams being directly put aside in favor of the men´s team. Validerat; 20151111 (global_studentproject_submitter)